Directory of Filipinists in Australia - May, Ronald. J.; Turner, Mark (Department of Political and Social Change, Australian National University, 1990)
"Philippine Studies Association of Australia (PSAA) was established in 1980 in order to promote academic work on the Philippines and to keep members informed of Philippine studies news." (Foreword) As the organization expanded, its members saw the need to create a directory for its growing number of members. It includes lists of Filipinists in Australia, former members of the PSAA (now overseas) and Australian groups such as non-governmental organizations having interests in the Philippines. Information was obtained mostly through questionnaires. With this directory, the publishers are hopeful to facilitate greater communication among PSAA members.